Effect of process parameters on the synthesis of silver nanoparticles and its effects on microbes - Yusof, Faridah; Chowdhury, Silvia; Sulaiman, Nadzril; Faruck, Mohammad Omer (UTM Press, 2018)
Metallic silver (Ag) and some Ag compounds have long being used to fight microbial infection even before the emergence of antibiotics in the form of drugs. But lately, one of the problems facing the medical world is the occurrence of drug resistance microbes. Therefore, actions must be taken to overcome the problem, one of which is to continue studies to develop new drugs, either synthetic or natural. The ultimate goal is to offer appropriate and efficient antimicrobial drugs to patients. In this regard, with the advent of nanotechnology, it is now possible to synthesize nano scale Ag which can be used in diverse medical applications. The aim of this study is to investigate the effect of some important parameters towards the production of high yield Ag nanoparticles (AgNPs) from silver salts by making use of reducing agent. One-Factor-at-a-Time (OFAT) design of experiment was conducted, involving five important synthesis parameters. Based on the analyses of its yellow color, absorption by UV-vis in the range of 350 to 420 nm wavelength and surface plasmon resonance (SPR) at 420 nm, AgNPs produced were estimated to be in the range of 5 to 50 nm in diameter. Out of the five parameters tested, such as the concentration of silver nitrate (AgNO3), the initial pH of AgNO3 solution, the concentration of tri-sodium citrate (TSC), the reaction time between AgNO3 and TSC and stirring time (after reduction process), results showed that all factors except stirring time affect the production. Characterization of AgNPs, carried out using Transmission Electron Microscope (TEM), showed that the synthesized AgNPs were spherical with diameters less than 15 nm. Antimicrobial activity assays of AgNPs, carried out against selected microbes, namely Aspergillus niger, Microsporum canis and Staphylococcus aureus showed various degree of potencies.